Regenerating pasture legumes in crop rotations - Riffkin P.; Evans P.; Chin J.; Wright A.; Cameron N. (Legumes for Mediterranean forage crops, pastures and alternative uses, 2000)
Twelve pasture legumes were assessed in the high rainfall region of south-eastern Australia (700 mm average annual rainfall) for their capacities to improve the grain yields of subsequent wheat crops. The ability of these legumes to regenerate following the crop phase was also examined. Pasture-legume dry matter yields in the year proceeding the crop was positively correlated with grain yield, possibly due to higher amounts of nitrogen fixed and improved soil structure. Trifolium michelianum, T. resupinatum, and T. subterranean were considered to be suitable as leys in pasture-crop rotations due to their abilities to regenerate following the crop phase.
10. Meeting of the Mediterranean Sub-Network of the FAO-CIHEAM Inter-Regional Cooperative Research and Development Network on Pastures and Fodder Crops, 2000/04/04-09, Sassari (Italy)